A Study of The Relationships between Compensation Package, Work Motivation and Job Satisfaction - Francis Mukemba Mwau; Nurul Fatihah binti Abdullah; Imron Sama Ae (Proceeding International Conference on Information Technology and Business, 2019)
In the error of industry 4.0 organizations are trying really hard to motivate and sustain their staff due the stiff competition witnessed. To motivate people to cope to with a variety of organizational work and changes in the dawn of fourth industrial revolution, the science of motivation remains the key answers. This research review aims at expounding on the theories of motivation and job satisfaction that are most suitable in the error of industry 4.0. we will introduce Herzberg two factor theory and Adams equity theory. By analysing the two theories we find that elements of motivation and job satisfaction have shifted from money-oriented factors. Therefore, this this research concludes that for employees to be satisfied, the managers need to eliminate dissatisfaction experienced by the employees and then help them find satisfaction. Employees will be highly motivated if they perceive their ratio of input is proportional to the ratio of outcome and that their input -outcome ration is fair compared to input -output ratio of their competitors.Keywords: Job satisfaction, Motivation